Results of autologous venous blood injections in plantar fasciitis: a prospective clinical study - Bhat, Khurshid Ahmad; Bhat, Suhail Ahmad; Muzaffar, Khalid; Haseeb, Muhammad (International Journal of Research in Medical Sciences, 2017)
Background: Plantar fasciitis is a degenerative disease of plantar fascia and is one of the most common causes of heel pain. The response to any treatment modality is unpredictable. The autologous blood might induce healing in the areas of degeneration by providing cellular and humoral components. The aim of this study was therefore to evaluate the results of autologous blood injection in plantar fasciitis. Methods: Thirty-two patients (average age of 42.4 years), 14 males (43.7%) and 18 females (56.2%) with history of chronic heel pain of more than 6 months duration were taken up for autologous blood injection. All the patients in this study were clinically evaluated and the visual analogous pain score was calculated from each patient pre-procedure and at 3 and 6 months after the procedure. Results: There was a significant improvement in VAS pain score in this study. Pre-procedure VAS pain score of 6.9 (average 4-10) was reduced to a mean score of 4.28 (average 0-9) at 3 months and a mean score of 3 (average 0-9) at 6 months. Conclusions: Autologous blood is an effective method of controlling pain in patients with plantar fasciitis.